2009
DOI: 10.1179/174313209x405137
|View full text |Cite
|
Sign up to set email alerts
|

A long-term follow-up of botulinum toxin A in cervical dystonia

Abstract: These data confirm the efficacy and safety of BoNT-A treatment in CD over an extended period of up to 14 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 27 publications
10
38
1
3
Order By: Relevance
“…Evidence of maintained response in this study is consistent with a previous long-term observational study, whereby the extended efficacy of Dysport (mean dose: 389 ± 144 U) was demonstrated in 163 (of a total population of 207) patients with CD who had received treatment for up to 14 years [11]. Maintenance of efficacy with Dysport is further supported by a long-term study of 108 patients with CD [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Evidence of maintained response in this study is consistent with a previous long-term observational study, whereby the extended efficacy of Dysport (mean dose: 389 ± 144 U) was demonstrated in 163 (of a total population of 207) patients with CD who had received treatment for up to 14 years [11]. Maintenance of efficacy with Dysport is further supported by a long-term study of 108 patients with CD [10].…”
Section: Discussionsupporting
confidence: 87%
“…Dysphagia was the most common AE, was mild in all reported cases, and did not lead to treatment discontinuation. The favorable tolerability profile of Dysport in this study is in agreement with both short-and long-term controlled and observational studies in patients with CD [7,8,10,11].…”
Section: Long-term Bont-a For Cervical Dystonia 357supporting
confidence: 89%
“…While other long-term studies have been reported, these were generally conducted retrospectively26 27 or did not assess clinical efficacy outcomes at the peak effect of treatment 7…”
Section: Discussionmentioning
confidence: 99%
“…Response rates of approximately 80% have been achieved in patients with CD in open and double-blind studies [9][10][11] . Furthermore, treatment is generally well tolerated even following long-term administration 12,13 and the risk of adverse events may also be minimized using well-defined injection procedures.…”
Section: Introductionmentioning
confidence: 99%